A tough and robust hydrogel constructed through carbon dots induced crystallization domains integrated orientation regulation - Huanxin Huo; Jingjie Shen; Jianyong Wan; Haoran Shi; Hongxing Yang; Xin Duan; Yihong Gao; Yumeng Chen; Feng Kuang; Hongshan Li; Long Yang; Guanben Du (Nature Communications)
Abstract Tough hydrogels show great potential applied in flexible electronics, sensors and soft robotics, but it remains challenging to combine high strength, toughness and stability. Here, we report the use of carbon dots (CDs) to induce the formation of crystalline domains, to give materials with favourable properties. The CDs act as nanoscale nucleation-sites within polyvinyl alcohol hydrogels, forming dense crystalline domains that serve as physical crosslinking sites. These domains enable a “pinning effect” that enhances energy dissipation and restricts crack propagation. The resulting hydrogels exhibit strong mechanical performance, including tensile strength up to 156 MPa and toughness of 225 MJ m-3, while also maintaining good swelling resistance. This strategy is generalizable across different types of CDs and polymer systems. In addition, the hydrogels demonstrate stable conductivity under water, making them suitable for applications in underwater motion sensing and flexible supercapacitors. This work provides a scalable approach to engineer robust, multifunctional hydrogels.